VD_FINDINFO 172/II vom 11. September 2009 - VD Tribunal cantonal (2009)
CERTIFICAT D'HÉRITIER, TESTAMENT, HÉRITIER, HÉRITIER INSTITUÉ, INSTITUTION D'HÉRITIER | 483 CC, 556 CC, 559 al. 1 CC, 559 al. 2 CC, 559 CC, 535 al. 3 CPC, 538 al. 1 CPC